"They are not Alone": Mentoring Women Graduate Students. Issue 5 (26th September 2022) - Griffith, Emily; Sharp, Julia
Abstract: Women and other historically marginalised groups can feel out of place on advanced degree programmes – mentoring can help. Here, Emily Griffith and Julia Sharp – both winners of the Outstanding Mentor Award from the ASA's Statistical Consulting section – show how